Do Disease Parameters Related to Primary Sjögren's Syndrome have an Impact on the Severity of Co-Existing Fibromyalgia Syndrome or Vice Versa? - Kaban, Nedim; Bakay, Umut; Soylu, Ali Can; Gürer, Gülcan; Harman, Halil (Aktuelle Rheumatologie, 2024)
Objectives We aimed to examine whether primary Sjögren's syndrome (pSS)-related parameters may affect the severity of co-existing fibromyalgia syndrome (FMS) in pSS patients or vice versa; co-existing FMS might have an influence on the severity of sicca symptoms and disease activity measurements in pSS.Method Our study included a total of 49 pSS patients (24 with concomitant FMS; 25 without FMS) and 30 patients with primary FMS (pFMS). The EULAR Sjögren's Syndrome Patient Reported Index (ESSPRI) and the EULAR Sjögren's Syndrome Disease Activity Index (ESSDAI) were used to evaluate pSS symptoms and disease activity. Sicca symptom severity (SSS) scores were recorded on a visual analogue scale for pSS patients. A minor salivary gland biopsy was performed in 34 pSS patients. The Revised Fibromyalgia Impact Questionnaire (FIQR) was used to evaluate the total spectrum of fibromyalgia-related problems.Results There was no statistically significant difference between disease activity measurements (ESSDAS, ESSPRI) in pSS patients with FMS and pSS patients (p=0.913, p=0.952, respectively). However, SSS scores were significantly higher in pSS patients with FMS than in pSS patients (p=0.045). There was no statistically significant difference between pFMS and pSS patients with FMS in terms of FIQR scores (p=0.149).Conclusions It was demonstrated that the severity of fibromyalgia assessed by FIQR is comparable between both groups.
Keywords: Fibromyalgie; Speicheldrüse; Sjögren-Syndrom; Xerophthalmie; Xerostomie